easy, just like the directions say
x+2y=10
x=10-2y so
3(10-2y)+4y=8
30-6y+4y=8
-2y= -22
y=11 so
x+2(11)=10
x+22=10
x= -12
2007-07-25 04:59:49
·
answer #1
·
answered by jnice160 2
·
0⤊
1⤋
Solve x:
x + 2y = 10
x = 10 - 2y
Solve y (substitute x)
3(10 - 2y) + 4y = 8
30 - 6y + 4y = 8
- 2y = 8 - 30
- 2y = - 22
y = 11
Solve x (substitute y):
x = 10 - 2(11)
x = 10 - 22
x = - 12
Answer x = - 12, y = 11
Proofs:
- 12 + 2(11) = 10
- 12 + 22 = 10
3(- 12) + 4(11) = 8
- 36 + 44 = 8
2007-07-28 21:15:46
·
answer #2
·
answered by Jun Agruda 7
·
2⤊
0⤋
subtract 2y to the different area you get x=-2y+10 plug it into the different equation 3(-2y+10)+4y=8 -6y+30+4y=8 -2y+30=8 -2y=-22 y=eleven plug y into the different and get x x+2(eleven)=10 x+22=10 x=-12
2016-11-10 07:05:20
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
Hey there!
Here's the answer.
x+2y=10 --> Write the first equation.
x=10-2y --> Subtract 2y on both sides of the equation.
3x+4y=8 --> Write the second equation.
3(10-2y)+4y=8 --> Substitute 10-2y for x.
30-6y+4y=8 --> Distribute 3 into 10-2y.
30-2y=8 --> Add -6y and 4y.
-2y=-22 --> Subtract 30 on both sides of the equation.
y=11 --> Divide both sides of the equation by -2.
x+2y=10 --> Write the first equation.
x+2(11)=10 --> Substitute 11 for y.
x+22=10 --> Multiply 2 and 11.
x=-12 Subtract 22 on both sides of the equation.
So the answer is x=-12 and y=11, or it can be written as a set {-12,11}.
Hope it helps!
2007-07-25 05:23:41
·
answer #4
·
answered by ? 6
·
0⤊
0⤋
x + 2y = 10 --1st eq'n; 3x + 4y = 8 --2nd
from the 1st eq'n, transpose 2y
x = 10 - 2y --3rd eq'n
substitute this to the 2nd eq'n
3(10 - 2y) + 4y = 8
30 - 6y + 4y = 8
transpose 30
-6y + 4y = 8 - 30
-2y = -22
divide the eq'n by -2 to solve for y
y = 11 ***
substitute y = 11 in 3rd eq'n
x = 10 - 2(11)
x = 10 - 22
x = -12 ***
2007-07-25 05:08:58
·
answer #5
·
answered by ned 2
·
0⤊
0⤋
x+2y=10
rearrange the equation and u get
x=10-2y -------- (1)
3x+4y=8 -------- (2)
sub (1) into (2)
3(10-2y)+4y=8
30-6y+4y=8
2y=22
y=11
sub y=11 into (1)
x=10-2(11)
x=-12
2007-07-25 05:12:45
·
answer #6
·
answered by þíиky ツツツ じò ぴé MufÇ 6
·
0⤊
0⤋
x=-2y+10 now sub 2nd 3( -2y + 10 ) + 4y = 8
-6y + 30 = 8 -6y = -22 y= 3 2/3so x=2 2/3
2007-07-25 05:06:17
·
answer #7
·
answered by dwinbaycity 5
·
0⤊
0⤋
(x+2y=10
(3x+4y=8
Equation I:
x = 10 - 2y
Substitution in Equation II:
3(10 - 2y) = 4y = 8
30 - 6y + 4y = 8
-2y = 8 - 30
y = -22 : -2
y = 11
x = 10 - 22
x = -12
Solution:{(-12 and 11)}
>$<
2007-07-25 05:01:35
·
answer #8
·
answered by aeiou 7
·
0⤊
1⤋
x = 10 - 2y
3(10 - 2y) + 4y = 8
30 - 6y + 4y = 8
30 - 2y = 8
2y = 22
y = 11
x = 10 - 22
x = - 12
x = - 12 , y = 11
2007-07-25 05:01:27
·
answer #9
·
answered by Como 7
·
0⤊
1⤋
x+2y=10
x=10-2y
3x+4y=8
3(10-2y)+4y=8
30-6y+4y=8
-2y=8-30
-2y=-22
y=22/2
y=11
x=2*11+10
x=32
2007-07-25 05:02:14
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋